A Clinical Study on Efficacy of Jivaniya Ghritapana in Shushkakshipaka (Dry Eye Syndrome) (International Journal of Ayurveda and Pharma Research, 2022)
Dry eye syndrome is a disease commonly seen in all age groups with a greater ration in elderly population. Large scale studies have determined that increasing age, female sex, and Asian race are all associated with higher DED prevalence. Their occurs tear deficiency and ocular surface disorders, which produces symptoms like discomfort, visual disturbance and tear film instability. Clinically and etymologically, similar entity to Dry eye syndrome is Shushkakshipaka. In modern ophthalmology, conventional approach for Dry eye syndrome is lubricating eye drops which are not satisfactory. Ayurveda has a holistic approach to deal with this problem. This clinical study was done to evaluate the effect of Jivaniya Ghritapana in Shushkakshipaka (dry eye syndrome). An open clinical trial for 10 patients was planned. They were presenting with clinical features of Shushkakshipaka (Dry Eye Syndrome). Snehapana was done in all patients with Jivaniya Ghrita. Results: On assessing the selected criteria, significant results were found in subjective parameters like Rukshta (feeling of dryness), Gharshana (gritty sensation), Daruna vartmakshi (hardness of eyelids), Karachaunmilana (difficulty in opening and closing of eyes), Daha (burning sensation) & intolerance to light. Significant result was found in all objective parameters. Conclusion: Thus we can conclude that, for successful treatment Shushkakshipaka (Dry Eye Syndrome), Snehapana can be advised in such patients.